Nitrous oxide exerts rewarding effect via regulating D1 receptor and BDNF pathway in ventral tegmental area-nucleus accumbens dopamine circuit - Wen-Qi Li; Sheng-Nan Liu; Si-Chang Yang; Xiang Lin; Zhang-Jin Zhang (Translational Psychiatry)
Abstract Recreational use of nitrous oxide (N2O) has risen dramatically over the past decades. This study aimed to examine its rewarding effect and the underlying mechanisms. The exposure of mice to a subanesthetic concentration (20%) of N2O for 30 min for 4 consecutive days paired with N2O in the morning and paired with the air in the afternoon produced apparent rewarding behavior in the conditioned place preference (CPP) paradigm. This was abrogated by microinjection into the nucleus accumbens (NAc) of the dopamine (DA) D1 receptor antagonist SCH23390, but not the D2 antagonist haloperidol. N2O robustly enhanced DAergic neuronal activity of the ventral tegmental area (VTA) and the concentration of DA in the NAc. The repeated N2O exposure also upregulated the expression of brain-derived neurotrophic factor (BDNF) in the VTA and its multiple downstream mediators in the NAc. Conversely, VTA focal knockdown of BDNF and the inhibition of the downstream mediators suppressed the N2O-induced rewarding effect and the DAergic neuronal activity of the VTA. Further, the combined intervention of BDNF knockdown and D1 antagonist significantly inhibited the N2O-induced rewarding effect in mice, which was greater than that of BDNF knockdown alone, but was not significantly different from that of D1 antagonist alone. These results indicate that the rewarding properties of N2O at subanesthetic concentration are associated with its upregulation of the VTA-NAc DA reward pathway probably via mediation of D1 receptor and BDNF/TrkB signaling. Among them, the modulation of BDNF may be the upstream of D1 receptor involved in N2O rewarding effect.